Anticancer effect of Indanone-based thiazolyl hydrazone derivative on p53 mutant colorectal cancer cell lines: An in vitro and in vivo study - Narayanan, Silpa; Teng, Qiu-Xu; Wu, Zhuo-Xun; Nazim, Urooj; Karadkhelkar, Nishant; Acharekar, Nikita; Yoganathan, Sabesan; Mansoor, Najia; Ping, Feng-Feng; Chen, Zhe-Sheng (Frontiers in Oncology, 2022)
Colorectal cancer is a major health problem, and it is the third most diagnosed cancer in the United States. The current treatment for colorectal cancer includes irinotecan, a topoisomerase I inhibitor, and other targeted drugs like bevacizumab and regorafenib. The low response rates and the incidences of high toxicity caused by these drugs instigated to evaluate the anticancer efficacy of a series of thirteen thiazolyl hydrazone derivatives of 1-indanone and four compounds among them showed favorable anticancer activity against some of the tested colorectal cancer cell lines with IC50 values ranging from 0.41 ± 0.19 to 6.85 ± 1.44 μM. It is noteworthy that one of the indanone-based thiazolyl hydrazone (ITH) derivatives, N-Indan-1-ylidene-N'-(4-Biphenyl-4-yl-thiazol-2-yl)-hydrazine (ITH-6), has a better cytotoxicity profile against p53 mutant colorectal cancer cells, HT-29, COLO 205, and KM 12 than p53 wild-type colorectal cancer cell line such as HCT 116. Mechanistic studies show that ITH-6 arrests these three cancer cell lines in G2/M phase and induces apoptosis. It also causes a rise in the ROS level with a remarkable decrease in the glutathione (GSH) level. Moreover, ITH-6 inhibits the expression of NF-κB p65 and Bcl-2, which proves its cytotoxic action. In addition, ITH-6 significantly decreased tumor size, growth rate and tumor volume in mice bearing HT-29 and KM 12 tumor xenografts. Moreover, CRISPR/Cas9 was applied to establish NF-κB p65 gene knockout HT-29 cell line model to validate the target of ITH-6. Overall, the results suggest that ITH-6 could be a potential anticancer drug candidate for p53 mutant colorectal cancers.